Branching Analysis of Comb‐Shaped Polystyrene with Long Chain Branches. Issue 12 (18th April 2017) - Lee, Sanghoon; Chang, Taihyun
Abstract : Chain branching analyses are carried out with well‐defined PS random combs with 1‐4 long branches in a good and a theta solvent, respectively. The relationship of g ′ = g ε ( g  ( R g 2 )B /( R g 2 )L, g ′  [η]B /[η]L ) works reasonably well with ε ~1 in tetrahydrofuran and ~0.66 in diethyl malonate while the theoretical g rw does not agree well with g exp . Abstract : Model comb‐shaped polystyrene (PS) samples are synthesized by anionic polymerization and the as‐prepared PS heterogeneous combs are further fractionated by temperature gradient interaction chromatography (TGIC) to obtain well‐defined random combs with 1–4 branches at random positions on a backbone. Size exclusion chromatography‐triple detection and TGIC‐triple detection analyses are carried out with the fractionated PS random combs in a good and a theta solvent, respectively. The experimentally observed geometric contraction factor ( g ), the ratio of the mean square radius of gyration and the hydrodynamic contraction factor ( g ′), and the ratio of the intrinsic viscosity are compared. It is observed that the two contraction factors follow the relationship of g ′ = g ε reasonably well and the exponent ε of the PS combs is found as ∼1 in a good solvent and ∼0.66 in a theta solvent. Furthermore, it is found that the theoretical g rw is not in good agreement with the experimental results.